Minimum wage or negative income tax: why skilled workers may favor wage rigidities - Maya Bacache-Beauvallet; Etienne Lehmann (Institute for the Study of Labor (IZA), 2005)
This article studies the political choice over the extent and the means of income redistribution between high and low skilled workers. Redistributive tools encompass fiscal transfers with negative income tax and minimum wage. Using fiscal instruments only is assumed optimal. We show that high skilled workers may favor a second-best minimum wage requirement. This is because minimum wage increases unemployment, hence the marginal cost of redistribution is higher which gives a pretext for high skilled workers to moderate low skilled workers claim for income redistribution.
Keywords: D78; E24; H23; J38; 330; unemployment; political economics; income redistribution; minimum wage